Ethno-Design-Based Learning Tools to Enhance Students' Future Thinking - Putu Okta Satriani; I Wayan Widiana; I Wayan Ardana (Journal for Lesson and Learning Studies, 2026)
The ability to think about the future is one of the important 21st century competencies that needs to be developed in elementary school students to face dynamic global challenges. However, the implementation of learning in elementary schools still tends to use conventional media and has not integrated interactive technology and local wisdom optimally. This research aims to develop and test the effectiveness of ethno design-based learning tools assisted by Augmented Reality (AR) in improving elementary school students' future thinking abilities. This research is development research using the ADDIE model involving fifth grade elementary school students as research subjects. Data collection was carried out through observation, interviews, questionnaires and tests with instruments in the form of expert validation sheets, teacher and student response questionnaires, as well as future thinking ability test questions. Data were analyzed using quantitative descriptive analysis and Paired Sample T-Test. The products developed include AR media "Subak Bali Interactive" and ethno design-based LKPD which integrates science and mathematics content. The research results show that the learning tools received the "Very Good" category in terms of validity and "Very Practical" based on teacher and student responses. The effectiveness test results show a significant increase in students' future thinking abilities after using the developed learning tools. This research concludes that AR-assisted ethno design-based learning tools are effective in creating contextual, interactive and future-oriented learning. The research implications show that this device can be an innovative alternative in supporting the strengthening of 21st century competencies in elementary school students.